The effect of Bi2O3/PbO substitution on physical, optical, structural, and gamma shielding properties of boro-tellurite glasses. (April 2023) - Marzuki, Ahmad; Sasmi, Tina; Fausta, Devara Ega; Harjana, Harjana; Suryanti, Venty; Kabalci, Idris
Abstract: Boro-tellurite glasses with molar compositions 60TeO2 –20B2 O3 -(20-x)Bi2 O3 -xPbO, where x = 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 mol% were fabricated using a standard melt quenching technique and studied in term of their physical, optical, structural and gamma shielding properties. As PbO concentration increases from 0 to 10 mol% (Bi2 O3 decreases), the density and molar volume of the present samples decrease from 6.08 to 5.93 gr/cm 3 and 33.37 to 30.27 cm 3 /mol, respectively. The optical packing density increases from 71.91 to 72.67% as PbO is added to the network to substitute Bi2 O3 . With the increase of PbO concentration, the refractive index, molar refractivity, and ionic polarizability decrease from 1.9137 to 1.8306, 18.531 to 16.884 cm 3, and 7.3534 to 6.7000 Å 3, respectively. The percentage of [TeO3] (tp) and [TeO3+1] polyhedra in the glass network increase with the rise of PbO concentration. The gamma radiation shielding features were analyzed theoretically using Phy-X PSD software with photon energies varied between 0.015 and 15 MeV. For all glasses, the highest linear attenuation coefficient (LAC) values are observed at 0.015 MeV while the lowest values are observed around 5 MeV, a turning point at which pair production starts to dominate the gamma photon-electron interaction. At all photon energies, the LAC values decrease with the increase in PbO concentration (the decrease in Bi2 O3 ). The LAC values at 0.015 MeV vary from 413.2183 to 12.4962 cm −1 . At low photon energies (0.015–0.04 MeV), this compositional dependence is high. Above 0.04 MeV, this dependence is low. This LAC result suggests that adding Bi2 O3 to the glasses is favorable for gamma shielding material as compared to PbO. Highlights: Glasses of 60TeO2 –20B2 O3 -(20-x)Bi2 O3 -xPbO (where x = 0–10 mol%) have been fabricated. Gamma shielding properties were theoretically studied using Phy-X PSD software. Bi2 O3 plays a bigger role in determining gamma shielding properties than PbO. Compositional dependency of LAC is stronger at low wavenumber. The present result may be important for the development of glass for gamma shielding.